Colitis Is Effectively Ameliorated by (±)-8-Acetonyl-dihydrocoptisine via the XBP1-NF-κB Pathway - Zhang, HaiJing; Song, GuangMing; Zhang, ZhiHui; Song, HuaChen; Tang, XiaoNan; Deng, AnJun; Wang, WenJie; Wu, LianQiu; Qin, HaiLin (Frontiers in Pharmacology, 2017)
Ulcerative colitis (UC) is a recurrent, chronic intestinal disease. Available treatments for UC are poor effective and/or cause severe adverse events. X-box binding protein 1 (XBP1) and nuclear factor-κB (NF-κB) have been reported to play important roles in UC. Specifically, deletion or downregulation of XBP1 leads to spontaneous enteritis and results in imbalanced secretion of NF-κB and other proinflammatory cytokines. (±)-8-acetonyl-dihydrocoptisine, i.e. (±)-8-ADC, is a monomer semi-synthesized from coptisine. In vitro, (±)-8-ADC activated the transcriptional activity of XBP1, inhibited expression of NF-κB, and reduced production of proinflammatory cytokines, such as tumor necrosis factor alpha (TNF-α) and interleukin-1 beta (IL-1β), in lipopolysaccharide (LPS)-stimulated IEC6 cells. Therefore, silencing XBP1 would reduce the inhibition effect of (±)-8-ADC on NF-κB expression and the cytokines secretion in vitro. In a dextran sulfate sodium (DSS)-induced colitis mouse model, oral administration of (±)-8-ADC ameliorated weight loss and colon contracture, and decreased the average disease activity index (DAI) score and pathological damage. Simultaneously, (±)-8-ADC also increased XBP1 expression, and decreased NF-κB expression and secretion of MPO, TNF-α, IL-6 and IL-1β in the colon. Therefore, (±)-8-ADC may ameliorate UC via the XBP1-NF-κB pathway and should be considered as a therapeutic candidate for UC.